EKSPLORASI DUNIA PERILAKU KREATIF: INOVASI, IMAJINASI, DAN PENGARUHNYA DALAM KEHIDUPAN SEHARI-HARI - M.Prayoga; Mochammad Isa Anshori (Kajian Ekonomi dan Akuntansi Terapan, 2024)
Creative behavior has an important role in the world of management and innovation, especially in the era of globalization and increasingly fierce business competition. This research aims to explore the world of creative behavior, focusing on aspects of innovation, imagination, and its influence in everyday life. In addition to having a significant impact in the realm of business and management, creative behavior also has a great influence in everyday life, covering various aspects such as art, education, health, and social relations. The importance of creative behavior in the context of management is emphasized, where innovation and imagination are vital triggers of creativity. Furthermore, this study aims to identify the factors that influence an individual's level of creativity, with the hope of making a tangible contribution to the development of innovative management strategies. Through a deeper understanding of these factors, leaders and management practitioners can develop a holistic approach to encourage creativity in the work environment. By integrating the results of this study into management practice, it is hoped that a work environment that facilitates creativity, innovation and sustainable growth can be created